2001
DOI: 10.1155/2001/213030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Articles on Neonatal Pain Published from 1965 to 1999

Abstract: Pain in neonates was a neglected subject of publication until the mid-1980s, and, currently, only a few countries seem interested in this type of pain. This lack of interest may be related to the undertreatment of pain in the neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Furthermore, the focus on acute pain in childhood might also be prevalent due to growing acknowledgment of the possible role of early life pain experiences in the development of chronic pain or altered pain processing [29]. Similar to earlier reviews [3,13], our findings show a continued increase in research on neonatal pain over time. This likely reflects the increased survival and need for care of preterm neonates and associated ubiquitous procedural pain exposure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the focus on acute pain in childhood might also be prevalent due to growing acknowledgment of the possible role of early life pain experiences in the development of chronic pain or altered pain processing [29]. Similar to earlier reviews [3,13], our findings show a continued increase in research on neonatal pain over time. This likely reflects the increased survival and need for care of preterm neonates and associated ubiquitous procedural pain exposure.…”
Section: Discussionsupporting
confidence: 81%
“…Prior reviews of the state of the field of pediatric pain research have shown a significant increase in published journal articles on pediatric pain over time, especially in neonates [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several recently published articles focused on the bibliometric characteristics of pain‐related research. Some focused on a specific syndrome, such as neonatal pain [4], headaches [5], and orofacial pain [6]. Some focused on a specific journal including Pain [7,8] and Clinical Journal of Pain [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pain in infancy has met increasing interest from the clinical and scientific society since the mid‐1980s (Banos et al. 2001).…”
mentioning
confidence: 99%
“…Colic has been studied in both psychological and paediatric research. In a meta‐analysis Banos et al. (2001) found that 20·4% of all scientific articles on neonatal pain, listed in MEDLINE 1965–1999, concerned colic pain.…”
mentioning
confidence: 99%